2011
DOI: 10.1186/1742-4690-8-95
|View full text |Cite
|
Sign up to set email alerts
|

Human HERC5 restricts an early stage of HIV-1 assembly by a mechanism correlating with the ISGylation of Gag

Abstract: BackgroundThe identification and characterization of several interferon (IFN)-induced cellular HIV-1 restriction factors, defined as host cellular proteins or factors that restrict or inhibit the HIV-1 life cycle, have provided insight into the IFN response towards HIV-1 infection and identified new therapeutic targets for HIV-1 infection. To further characterize the mechanism underlying restriction of the late stages of HIV-1 replication, we assessed the ability of IFNbeta-induced genes to restrict HIV-1 Gag … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 57 publications
0
81
1
Order By: Relevance
“…Because ISGylation has been reported to inhibit HIV-1 budding and release (Okumura et al, 2006; Pincetic et al, 2010; Woods et al, 2011), we evaluated the role of UBE2L6 in HIV-1 late-stage replication. We observed >65% inhibition of virion release 72 hr post-infection in UBE2L6-expressing cells as compared to cells expressing the vector control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because ISGylation has been reported to inhibit HIV-1 budding and release (Okumura et al, 2006; Pincetic et al, 2010; Woods et al, 2011), we evaluated the role of UBE2L6 in HIV-1 late-stage replication. We observed >65% inhibition of virion release 72 hr post-infection in UBE2L6-expressing cells as compared to cells expressing the vector control.…”
Section: Resultsmentioning
confidence: 99%
“…Host protein ISGylation has been implicated in cellular activities that restrict HIV-1 infection. Specifically, studies have demonstrated that HERC5, the E3 ligase component of the ISGylation machinery, reduces HIV-1 virion production through the aggregation of Gag at viral assembly sites in the membrane, which is distinct from the mechanism involving free ISG15 that results in Gag aggregation in both membrane and cytosolic regions of the cell (Woods et al, 2011). Additional mechanisms such as the inhibition of Gag and Tsg101 interaction by ISG15 (Okumura et al, 2006) have been implicated in regulating late-stage HIV-1 replication.…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition of replication was dependent on the ability of ISG15 to form conjugates as increased influenza B virus replication was also seen in mice that lack the ISG15 E1 activating enzyme, UbE1L, and thus fail to form ISG15 conjugates (24). Subsequent studies have demonstrated that ISG15 can antagonize the replication of vaccinia virus, influenza A virus, Sendai virus, human papillomavirus, Ebola virus, and HIV-1 in tissue culture to various degrees (23,(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
mentioning
confidence: 99%
“…HERC5 is a ligase that targets newly synthesized proteins for ISG15 conjugation and facilitates many cellular pathways. Woods et al showed that overexpression of HERC5 induced a fourfold decrease in HIV production in 293T cells and HERC5 knockdown doubled viral production (Woods et al 2011). By transmission electron microscopy, it was shown that HERC5 blocks an early step of HIV-1 particle assembly at the plasma membrane.…”
Section: Gag Assembly: Herc5mentioning
confidence: 97%